Chronic Skin Lesions as the Presentation of Diffuse Cutaneous Leishmaniasis in the HIV-Infected Woman: A Case Report and Review of Literatures: - Dalfardi, Behnam; Davarpanah, Mohammad Ali; Dehghanian, Amirreza; Akbari, Ali (Galen Medical Journal, 2019)
Background: Cutaneous leishmaniasis (CL) is the most form of leishmaniasis that caused by intracellular parasites, Leishmania. Case Report: A 39-year-old woman, known case of HIV infection, presented with a 6-month history of skin lesions initially on her face, then extending onto the chest, abdomen, and extremities. Laboratory examinations revealed leukopenia and a CD4 cell count of 280 cells / mm3. A biopsy was taken from skin lesions, and histopathological studies showed aggregates of macrophages filled with numerous Leishman bodies, the diagnosis of diffuse CL was confirmed. Consequently, she received liposomal amphotericin B (total dose of 40 mg/kg) as a case of diffuse CL. The skin lesions showed significant improvement after completion of treatment. Conclusion: Diffuse CL should be considered as a differential diagnosis in all patients with diffuse skin lesions mainly in the cases that suffer from disorders of cell-mediated immunity.[GMJ.2019;8:e1294]